Trans-generational mentorship : a challenge to pastoral care as life care - Oosthuizen, Johannes Jacobus (Stellenbosch : Stellenbosch University, 2008)
Thesis (MDiv (Practical Theology and Missiology. Divinity))--University of Stellenbosch, 2007.